Adverse Effects of Intraparenchymal and Peritumoral Application of Isosulfan Blue Dye in Sentinel Lymph Node Mapping in Breast Cancer: A Systematic Review and Meta-Analysis - Joshua Agilinko; Aditya Borakati; Andrel Yoong; Ponnuthurai Pratheepan; Suzette Samlalsingh (European Journal of Breast Health)
We investigate the evidence for adverse effects of intraparenchymal and peritumoral application of isosulfan blue dye in sentinel lymph node (SLN) mapping in breast cancer patients. A meta-analysis on the adverse effects of intraparenchymal and peritumoral application of isosulfan application in SLN mapping was conducted using Medline and Embase databases up to 2023. Procedure-based adverse reactions were divided into three grades: Grade I (allergic skin reactions), Grade II (hypotension) and Grade III (requiring vasopressor support). Heterogeneity was expressed with I-squared and tau statistics. Subgroup analysis was conducted for administrative route. Univariable meta-regression was performed to assess dose-response effect on adverse reactions. Sensitivity analysis was conducted using fixed effect modelling. A total of 19,183 patients were identified from eight studies. The pooled total adverse event rate after isosulfan administration was 11.65 events per 1,000 patients [95% confidence interval (CI) 7.44–18.19]. The rate of Grade I reactions was 7.96 per 1,000 (95% CI 4.08-15.46); Grade II 0.08 per 1,000 (95% CI 0.00–1.31), Grade III 1.86 per 1,000 (95% CI 0.94–3.66), with no reported mortalities. Intraparenchymal administration was associated with 15.16 events per 1,000 (95% 8.64–26.45), versus 7.04 events per 1,000 (95% CI 5.24–9.45) in peritumoral administration (p=0.02). Univariable meta-regression did not show a significant association between volume of dye infused and total adverse events (-0.164 events per mL, 95% CI -0.864 to 0.534, p=0.645). Isosulfan has low adverse event rates regardless of injection technique or volume administered. Clinicians should have a high level of confidence in its use as an agent for SLN mapping, especially when administering it peritumorally.